Predictive modeling of permeability loss at high-barium formation using symbolic regression - Saifi, Redha; Zeraibi, Nourreddine; Gareche, Mourad; Nait, Amar Menad; Benamara, Chahrazed (Zielona Góra: Uniwersytet Zielonogórski)
Mineral scaling is a common issue in oil recovery, causing severe formation damage and reduced permeability. This primarily results from chemical incompatibility between the injected and formation brines, which induces the precipitation of salts such as calcium carbonate, calcium sulfate, and barium sulfate. Accurate scale prediction is essential for managing operational risks and minimizing associated costs. in, this study, a symbolic regression technique based on evolutionary algorithms was employed to an explicit mathematical model linking permeability damage to key flow parameters.
Keywords: scaling; permeability loss; symbolic regression; sulfate barium; predictive modeling